Quality of End-Year Assessment Question Items for Islamic Religious Education & Character Subjects - Ningsih, Rahayu; Karnadi, Karnadi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to determine the quality of the End of Year Assessment (PAT) questions in Islamic Religious Education and Character Education subjects in class IX in Junior High School, Semarang City, for the 2022/2023 Academic Year in terms of level of difficulty, distinguishing power, effectiveness of distractors and reliability. This research is quantitative descriptive research; the subjects are class IX students for the 2022/2023 school year at SMP N 16 and SMP Islam Al-Azhar 29 Semarang, with 90 students from each school. The data collection technique used was observation, documentation, and testing techniques, and then the data obtained was analyzed using Anates Software version 4. The results of this research showed that the results of the analysis of the quality of the End of Year Assessment (PAT) questions for PAI and BP class IX subjects obtained: At SMP Negeri 16 Semarang, 20 questions are valid and can be stored in the school's question bank to be used in other tests relevant to PAI and BP subjects. In contrast, 20 questions are invalid and need to be improved to be used in subsequent tests. At Al-Azhar 29 Islamic Middle School Semarang, 15 questions are good. They can be stored in the school's question bank for other tests relevant to PAI and BP subjects, while 15 questions are invalid and need to be improved through revisions so that the items can be used in subsequent tests.